WRITING TOGETHER, LEARNING TOGETHER: BOOSTING STUDENT SKILLS THROUGH COLLABORATION - Ade Ismail; Indry Widyasti Anwar; Abdulhalim Daud (Indonesian EFL Journal, 2025)
This study aims to enhance students’ essay writing skills through the implementation of a qualitative learning model and to investigate their perceptions of the use of collaborative learning in the classroom. A total of 15 students participated in the study. The statistical test results indicated a significance value of p < 0.01, which is below the threshold of 0.05, demonstrating that the use of collaborative learning models in academic writing can significantly improve students’ writing skills. Students’ perceptions of collaborative writing were predominantly positive in terms of overall understanding, comprehension, knowledge exchange, and critical thinking. The mean scores for items 1, 2, 3, and 4 ranged from 3.13 to 3.33, suggesting that students largely perceived collaborative writing as having a positive impact on these aspects. Aspects related to participation, reflecting shared active contribution during collaborative writing activities (item 13) and problem solving by group members (item 3), were rated moderately at 3.13. This indicates that although students reported being engaged, some challenges may still have been encountered in achieving full participation throughout the process